Digital photography for everyone : LiveLessons - Rich, Jason (LiveLessons (Indianapolis, Ind.), 2011)
"Virtually all of the photography tips and strategies discusses and demonstrated throughout the course will work using any digital camera, including the camera built into many Smartphones and tablets, as well as all digital point-and-shoot cameras and Digital SLR cameras."--Resource description page.